(untitled) (Revista Logos Ciencia & Tecnología, 2019)
The Colombia National Police, selects, trains and certifies canine team, determining which dogs are Fit or Not Fit to start training, continue and verify its subsequent performance. Therefore, the objectives of this research were: 1). Determine the incidence of odor discrimination during the training and final certification of canine substances detectors and 2). Establish the correlation between odor discrimination, perseverance and alertness during "blind tests". The results prove the hypothesis that when performing blind tests in training, using real records and discriminating the smell, a greater number of canine equipment is obtained in the final certification. It is evident that the precision to discriminate target odors is 99% (percentage of detected targets) and specificity of 96% (percentage of correctly discriminated targets), with statistically significant results for the majority of the behavioral variables analyzed individually (P < 0,05) and a level of agreement between the evaluators (Kappa de Cohen) almost perfect for most of the tests, concluding that the warning signs in real contexts, carrying out the blind tests during the training and final certification, make the binomials to being exposed to noise, presence of people and other animals, improve their operational results.